The role of the media and digital scenarios in the exercise of citizen participation - Peña Orozco, Carlos Alberto
The objective of this article of reflection is to describe the role that media and digital scenarios have regarding citizen participation in the exercise of democracy, based on a thorough review of a specialized scientific bibliography that gives an account of the current state of the theme addressed. Although the bibliographic review showed as a main result a strong relationship between the need to link the media in the best way to the exercise of citizen participation, as well as the need to better exploit digital scenarios, it was concluded that it is not definitive that these scenarios make it possible for citizens to be heard and that their initiatives have the expected scope to influence political decisions.